Long Non-coding RNA IRAIN Inhibits VEGFA Expression via Enhancing Its DNA Methylation Leading to Tumor Suppression in Renal Carcinoma - Li, Yang; Luo, Qingyang; Li, Zun; Wang, Yun; Zhu, Chaoyang; Li, Tieqiang; Li, Xiaodong (Frontiers in Oncology, 2020)
Aims: Long non-coding RNA IRAIN (lncRNA IRAIN) plays a critical role in numerous malignancies. However, the function of lncRNA IRAIN in renal carcinoma (RC) remains enigmatic. The purpose of this study is to characterize the effects of lncRNA IRAIN on RC progression. Methods: The expression pattern of lncRNA IRAIN and the vascular endothelial growth factor A (VEGFA) in RC tissues and cells was characterized by RT-qPCR and Western blot analysis. The roles of lncRNA IRAIN and VEGFA in the progression of RC were studied by gain- or loss-of-function experiments. Bioinformatics data analysis was used to predict CpG islands in the VEGFA promoter region. MSP was applied to detect the level of DNA methylation in RC cells. The interaction between lncRNA IRAIN and VEGFA was identified by RNA immunoprecipitation and RNA-protein pull down assays. Recruitment of DNA methyltransferases (Dnmt) to the VEGFA promoter region was achieved by chromatin immunoprecipitation. The subcellular localization of lncRNA IRAIN was detected by fractionation of nuclear and cytoplasmic RNA. Cell viability was investigated by CCK-8 assay, cell migration was tested by transwell migration assay, and apoptosis was analyzed by flow cytometry. The expression of epithelial-mesenchymal transition-related and apoptotic factors was evaluated by Western blot analysis. Finally, the effect of lncRNA IRAIN/VEGFA axis was confirmed in an in vivo tumor xenograft model. Results: LncRNA IRAIN was poorly expressed in RC tissues and cells with a primary localization in the nucleus, while VEGFA was highly expressed. Overexpression of lncRNA IRAIN or, knock down of VEGFA, inhibited cell proliferation and migration and, induced the apoptosis of RC cells. Bioinformatics analysis indicated the presence of CpG islands in the VEGFA promoter region. Lack of methylation at specific sites in the VEGFA promoter region was detected through MSP assay. We found that lncRNA IRAIN was able to inhibit VEGFA expression through recruitment of Dnmt1, Dnmt3a and Dnmt3b to the VEGFA promoter region. LncRNA IRAIN was also able to suppress RC tumor growth via repression of VEGFA in an in vivo mouse xenograft model. Conclusion: Our data shows that by downregulating VEGFA expression in RC, the lncRNA IRAIN has tumor-suppressive potential.